Digital Crime in Bihar: Trends, Case Studies, and District-Wise Vulnerability Analysis in the Age of Expanding Connectivity - Ajit Kumar,; Prof. (Dr.) Om Prakash Roy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Bihar has witnessed a dramatic surge in digital (cyber) crimes in recent years, paralleling the rapid expansion of internet access and smartphones across the state [1][2]. While cybercrime was once a minor concern – with only 374 cases registered in 2018 – incidents have skyrocketed to thousands by the mid-2020s [3]. Official data show that 40,180 online financial fraud complaints were reported in 2023, which jumped to 67,380 in 2024 [4]. By 2024, Bihar’s cybercrime cell recorded 5,274 registered cybercrime cases, a massive increase from just a few hundred in 2018 [3]. This upward trend is attributed to greater digital adoption outpacing cybersecurity awareness, creating a “fertile breeding ground” for cyber scams in both urban and rural populations[5][6]. Several factors unique to Bihar exacerbate the risk. The state’s population is largely rural (over 70%), and digital literacy remains low even as services like online banking, mobile payments, and e-governance spread rapidly [1][6]. Low awareness and economic vulnerability have made even educated users fall prey to phishing links, OTP frauds, QR code scams, and fake investment schemes [8][9]. The COVID-19 pandemic accelerated the shift to online platforms, which brought new threats like sextortion, loan-app blackmail, and ransomware attacks, some of which struck institutional targets in Bihar. Notably, in 2023, ransomware crippled Patna municipal servers and a Bhagalpur hospital’s systems for weeks, highlighting an evolution from simple phone scams to more sophisticated cyber-attacks on infrastructure [10]. As criminals adopt spoofed caller IDs, deepfakes, and other social engineering tactics, law enforcement has had to step up accordingly [11]. The Bihar Police have responded with significant capacity-building. A specialized Economic Offences Unit (EOU) serves as the nodal cybercrime unit since 2011 [12]. In February 2023, a 24×7 cyber helpline (dial 1930) was launched, and by June 2023 the state opened 44 dedicated cyber police stations – one in each district – to ensure even rural victims can easily lodge cyber FIRs [13][14]. The impact of these measures is evident in improved reporting and prevention: in 2024 alone (up to November), over ₹394 crore in fraudulent online transactions were reported by victims and ₹66.17 crore successfully frozen by authorities (a 16.8% recovery rate) handling of cybercrime complaints rate) [15]. Bihar now ranks among the top states in India for proactive complaints [16]. Over 6,000 cybercrime FIRs were registered in 2024, placing Bihar third nationally in FIR count from cyber reports [17]. Police have also arrested hundreds of cybercriminals under Operation Cyber Prahar – 808 arrests since mid-2024 – through statewide raids and intelligence- driven operations[18] . Meanwhile, more than 7,300 police personnel have been trained in cybercrime investigation since 2018 [19]. These efforts reflect a robust institutional response even as cybercriminals continuously adapt their methods. In the sections below, we present detailed case studies of digital crimes in Bihar between 2023 and 2025, arranged in reverse chronological order. These real-world cases illustrate the diverse forms of cyber offenses – from online fraud and hacking to novel scams unique to Bihar’s socio-economic context – and the corresponding law enforcement actions. We then analyze the geographic distribution of cybercrime across Bihar’s districts, including a comparison with population and literacy factors, to understand patterns and vulnerabilities (with figures for visualization).
Keywords: cybercrime; Bihar; digital fraud; cybersecurity; ransomware; phishing; law enforcement